Identification of recently identified tick-borne viruses (Dabieshan tick virus and SFTSV) by metagenomic analysis in ticks from Shandong Province, China. Issue 6 (December 2020) - Shao, Lijun; Pang, Zheng; Fu, Hongchen; Chang, Ruiheng; Lin, Zuomiao; Lv, Aiqun; Wang, Shenghan; Kong, Xiangbing; Luo, Meihui; Liu, Xing; Yu, Xiaoli; Liu, Lin; et al.
Abstract: The aim of this study is to systematically examine the variety of viruses maintained in ticks from Shandong Province. A total of 2522 ticks were sampled from five cities of Shandong Province and divided into 264 pools according to location and species. Viral megagenomic analysis revealed the sequences of two viruses, Dabieshan tick virus and SFTSV. Then qRT-PCR and nested PCR were performed to confirm the presence of corresponding pathogens, which showed positive results for Dabieshan tick virus and SFTSV, with a minimum infection rate of 0.67% (17/2522) and 2.5% (63/2522), respectively. Phylogenetic analysis showed that Dabieshan tick virus formed a monophyletic cluster with the Yongjia tick virus and Uukuniemi virus from China, and SFTSV shared over 95% identity with human and animal derived isolates. These findings are the first time to demonstrate molecular evidence of Dabieshan tick virus in unrecognized endemic regions and indicate the need for further investigation.